Can the Treatment of Limit Orders Reconcile the Differences in Trading Costs between NYSE and Nasdaq Issues? - Chung, Kee H.; Ness, Bonnie F. Van; Ness, Robert A. Van (Journal of Financial and Quantitative Analysis, 2001)
In this paper, we determine whether each bid (ask) quote reflects the trading interest of the specialist, limit order traders, or both for a sample of NYSE stocks in 1991. We then compare Nasdaq spreads with NYSE spreads that reflect the trading interest of the specialist. Our empirical results show that the average Nasdaq spread is significantly larger than the average NYSE specialist spread. We find that, on average, 49% of the difference between Nasdaq and specialist spreads is due to the differential use of even-eighth quotes between Nasdaq dealers and NYSE specialists. We also find that the NYSE specialist spread is significantly larger than the limit order spread, although NYSE specialists and limit order traders are similiar in their use of even-eighth quotes.